Answer :

Given

11^{th}term = 38

⇒ a + (11-1)d = 38 → __1__

16^{th} term = 73

⇒ a + (16-1)d = 73 → __2__

By subtracting the both equations we will get ‘d’

(a +10d) – (a+15d) = 38 -73

-5d = -35

d = 7

By substituting “d” in equation __1__

a +10d = 38

a + 10×7 = 38

a = -32

a_{31} = a + (31-1) d

= -32 + 30×7

= 178

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Find the</sAP- Mathematics

Find the</sAP- Mathematics

Find the reAP- Mathematics

Find the reAP- Mathematics

Find the reAP- Mathematics

Find the reAP- Mathematics

Find the 31AP- Mathematics

How many muAP- Mathematics

How many thAP- Mathematics

Subba Rao sAP- Mathematics